Clinical implementation of a log file-based machine and patient QA system for IMRT and VMAT treatment plans. (April 2023) - Silvestri, Valerio; Raspanti, Davide; Guerrisi, Maria Giovanna; Falco, Maria Daniela
Highlights: MCS based classification of H&N, prostate, rectum and breast radiotherapy plans. MCS allows physicists to find over/under-modulated plans before pre-treatment QA. Sensitivity comparison between LINACWatch and Octavius 4D. LINACWatch is more sensitive when compared to Octavius 4D: 48.5% vs 30.4%. Logfile-based QA can be considered an useful complement to phantom-based QA. Abstract: Purpose: To determine the error detection sensitivity of a commercial log file-based system (LINACWatch®, LW) for integration into clinical routine and to compare it with a measurement device (OCTAVIUS 4D, Oct4D) for IMRT and VMAT delivery QA. Materials and methods: 76 VMAT/IMRT plans (H&N, prostate, rectum and breast) preliminarily classified according to their Modulation Complexity Score (MCS) calculated by LW, were considered. Receiver Operating Characteristic (ROC) Curves were used to establish gamma criteria for LW. 12 plans (3 for each site) were intentionally modified in order to introduce delivery errors regarding MLC, jaws, collimator, gantry and MU (for a total set of 168 incorrect plans) and irradiated on Oct4D; the corresponding log files were analysed by LW. Each incorrect plan was compared to the error-free plan using γ-index analysis for MLC, jaws and MU errors investigation and Root-Mean-Square (RMS) values for gantry and collimator errors investigation. Results: MCS ranges values were: 0.10–0.20 for H&N, 0.21–0.40 for prostate and rectum, 0.41–1.00 for breast. From ROC curves, the Gamma Passing Rate (GPR) thresholds were: 87%, 92%, 99% for H&N, prostate and rectum, and breast, respectively. The 1.5%/1.5 mm/local criteria were adopted for the γ-analysis. LW sensitivity in detecting the introduced errors was higher when compared to Oct4D: 48.5% vs 30.4% respectively. Conclusions: LW can be considered useful complement to phantom-based delivery QA of IMRT/VMAT plans. The MCS tool is effective in detecting over or under modulated plans prior to pre-treatment QA. However, rigorous and routinely machine QCs are recommended.